Targeted treatment approaches in refractory germ cell tumors - Gálvez Carvajal, Laura; Sánchez-Muñoz, Alfonso; Ribelles, Nuria; Saez, Maribel; Baena, Javier; Ruiz, Sofía; Ithurbisquy, Catherine; Alba-Conejo, Emilio (Elsevier, 2019)
Germ cell tumors (GCTs) are the most common type of solid tumor amongst patients between 15 and 35 years of age. They are also one of the types of tumor with the highest cure rate, due to their high sensitivity to cisplatin based chemotherapy. Nonetheless, around 15-20% of metastatic patients will not have curative options after a relapse on the first and second line. This proves that new therapeutic options for these refractory GCTs patients need to be developed. This article offers a bibliographic review of all studies using targeted treatment or immunotherapy for refractory GCTs patients.
Este artículo ha sido publicado en la revista Crit Rev Oncol Hematology This article is available under the Creative Commons CC-BY-NC-ND license and permits non-commercial use of the work as published, without adaptation or alteration provided the work is fully attributed. Les adjunto articulo y la respuesta de la revista si lo necesitan les puede hacer llegar toda la cadena de e mail Dear Dr. Alfonso sanchez muñoz, Thank you for the email. I could see that this is a published article (ONCH 2813). Below is the link to the published final version. Targeted treatment approaches in refractory germ cell tumors - ScienceDirect When you click this link, it would take you to the article in science direct, there you could see a link named "Get rights and content" Appended below is the screenshot. Please use this link to get all rights for this published article.
Keywords: Células germinales - Tumores; Germ cell tumors; Targeted therapy; Testicular tumors